Hillary Clinton and the reflection of American values – a new concept = Hillary Clinton và sự phản ánh giá trị văn hóa Mỹ - khái niệm mới - Phạm, Phương Hoa (2020)
Understanding traditional American values is an ideal way to understand how Americans are thinking and behaving. Nowadays, many Americans still believe in them and are strongly affected by them in every facet of their everyday lives. Meticulously investigating the life of an outstanding American politician would be an effective way to directly immerse in the American values. Conducting this research, the researcher expected to gain an in-depth understanding of American values reflected through the life of Hillary Rodham Clinton, one of the most influential women in the political life of America. Moreover, the researcher desired to explore new concepts of American values hidden in Hillary’s ambitions and behaviors through a number of significant events. With the purpose of finding valid and reliable results, the method of narrative analysis and content analysis were intensively employed in this research. Data for the study was collected mainly from three published books, namely “Living history” (2003), “A woman in charge” (2007) and “Her way” (2007). Relevant information about Hillary’s personalities was carefully analyzed on the base of two research questions. The researcher also collected and analyzed data from a wide range of other sources, such as online journals and articles, together with a number of Hillary’s speeches and public statements on YouTube in order to increase the sufficiency of the study. Hillary Rodham Clinton had traveled an extraordinary and uniquely American journey as a pioneering woman, as Bill’s spouse and political partner, as a First Lady and as a U.S Senator. Through every tweak in her public image, Hillary herself has been the meticulous architect of her persona as a personification of American values.